Evaluating soil rhizobacteria for their ability to enhance plant growth and tuber yield in potato - Oswald, A; Calvo Velez, P.; Zúñiga Dávila, Doris Elizabeth; Arcos Pineda, Jesus Heraclides (Wiley-Blackwell Publishing Ltd, 2023)
The objectives of this study were to identify promising microorganisms to improve potato productivity in low-input systems of tropical highlands and to compare results from in vitro, greenhouse and field experiments to advance the development of a screening method for rhizobacteria and develop an efficient assessment of their effect on plant growth in field conditions. A total of 150 bacterial strains were screened in vitro, in greenhouse and field trials. The series of experiments confirmed the plant growth-promoting ability of a range of rhizobacteria. Although in vitro and greenhouse results were promising, the field experiment showed variability and the results require further verification. The in vitro tests might have limited value for screening as no correlation could be found between in vitro tests and pot trial results. However, trials in controlled conditions produced insights into the mechanisms causing better plant growth in potato, such as early tuberisation, fast development of leaf area and probably greater photosynthetic rates.